The temporality of dwelling in Christian Papua New Guinea - Van Heekeren, Deborah (The Australian journal of anthropology, 2025)
When Papua New Guinea (PNG) gained independence in 1975, the Constitution of the Independent State of PNG proclaimed that it was Christian. In the coastal areas, where the mission project had been underway for almost a century, commentators were proclaiming the widespread ‘success’ of Christianity. As anthropology entered the new century, the increase in attention to Christianity gained impetus driven largely by the arrival of evangelical churches. My work with the Vula'a of south-eastern PNG suggests that attention to the significance and scale of church building might contribute to understanding the perceived success of Christianity. Drawing on Tim Ingold's phenomenology of landscape as it is informed by Martin Heidegger's concept of dwelling—that we build and have built because we dwell—I propose that the ethnography of village Christianity is an exemplary study of dwelling as a fundamental mode of being Christian in PNG.